Synchrotron studies of "self-compression" in urea inclusion compounds - Wang, Bo (Kansas State University, 2017)
Urea inclusion compounds (UICs) are classic examples of nanoporous, host:guest materials in which the linear channels of the honeycomb structure of the urea host can include various types of long-chain compounds (the guests). By using synchrotron X-ray radiation sources, a deeper understanding of these materials is made possible through detailed structural studies. In particular, this dissertation describes a series of structural phase transitions that occur upon cooling two related UICs containing alkanedione guest molecules. UICs may be classified as either commensurate or incommensurate structures, depending on whether the repeat lengths of the host (c[subscript h]) and guest (c[subscript g]) along the channel axis are related by a small whole number ratio. Crystals of 2,8-nonanedione/urea and 2,11-dodecanedione/urea, which are incommensurate structures at room temperature, undergo "lock-in" phase transitions below room temperature to generate commensurate structures in which the guest repeat lengths are elongated. Upon nucleation and growth of these elongated, commensurate phases, other molecules in the same channels are compressed to give successively shorter guest repeat lengths. Further lock-in phase transitions give a multitude of commensurate and incommensurate phases during cooling. The crystal structures of two of these commensurate phases have been determined using synchrotron sources. The "self-compression" observed in these 1-D crystals serves as a paradigm for understanding solid-state reactions in three-dimensional crystals.
Keywords: Synchrotron X-ray; Urea inclusion compounds; Phase transition